ANALISIS EFISIENSI BELANJA DAERAH PEMERINTAH PROVINSI JAMBI TAHUN 2011 - Fathiyah Fathiyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
Analysis of Jambi Provincial Government Expenditure In 2011 performed using Analysis of Variance, Growth Ratio Analysis, Ratio Analysis Harmony Shopping, Spending Efficiency Ratio Analysis, and Ratio Analysis Expenditure to GDP.The results of the analysis of all the ratios above indicate that there is efficiency in all parts of regional spending in 2011, and in accordance with the concept of value for money. Overall mean performance Jambi Provincial Government budget year 2011 rated as good.Keyword : Local Expenditure anylisis, Local Expenditure Ratio, Efficiency.